Fabrication and characterization of Ca2+, Sr2+, Ba2+, Sm3+, and La3+ co-doped ceria-based electrolyte powders for low-temperature anode-supported solid oxide fuel cells. (27th September 2018) - Wu, Yu-Chuan; Chen, Wan-Yu
Abstract: In this study, CeO2 -based electrolytes are synthesized by a sol-gel method. Ce0.8 Sm0.2 O1.9, Ce0.8 Sm0.15 Ca0.05 O1.875, Ce0.8 Sm0.15 Ca0.025 Sr0.025 O1.875 (S15CS05DC), Ce0.8 Sm0.15 La0.05 O1.9, (La0.77 Sr0.2 Ba0.03 )0.15 Ce0.85 O1.908, and (La0.77 Sr0.2 Ba0.03 )0.2 Ce0.8 O1.877 specimens are prepared at sintering temperature 1300 °C for either 2 h or 4 h. The microstructures and electrical properties of the electrolytes are analyzed using X-ray diffraction, scanning electron microscopy, and alternating current (AC) impedance spectroscopy. All samples are cubic fluorite structure. It is found that while Ca 2+ and Sr 2+ contribute to grain growth, Sm 3+ and La 2+ inhibit it. The conductivity increases with temperature in a linear manner and reaches approximately 0.16 S·cm − 1  at 800 °C for the 4 h-sintered S15CS05DC sample. Six anode-supported cells are fabricated and tested at 600 °C–800 °C. Cell-C has the highest maximum power density (0.96 W·cm −2 ) at 800 °C. It is also found that ohmic resistance predominantly determines the total cell resistance at temperatures above 700 °C. Highlights: The multi-elements co-doped CeO2 were successfully synthesized by a sol-gel method. The cells have successfully fabricated by co-sintering at 1300 °C for 4 h. The conductivities of the multi-elements co-doped CeO2 electrolytes were studied. The S15CS05DC–4 cell has the highest maximum power density (0.96 W·cm −2 ) at 800 °C.